Pregnancy rate and associated factors in dairy cows of Bangladesh - Amin, MAN Al; Arman, SM; Afrose, M; Rahman, MM; Bhattacharjee, J; Bhuiyan, MMU (Bangladesh Veterinarian, 2019)
The study was undertaken to identity the factors affecting the pregnancy rate in cows of commercial dairy farms in Bangladesh. Pre-tested questionnaires were used for collecting data from 662 mixed breed cows of 22 commercial dairy farms. The overall pregnancy rate was 53.6%. Pregnancy rate was the highest (62.5%) in local breed (P<0.05) followed by pure Friesian (55.5%), Local  Friesian (53.2%), Sahiwal  Friesian (54.5%) and Local  Jersey (50.0%) breed. The cows between 37 and 72 months old had higher pregnancy rate (58.9%) than cows aged 18 to 36 (44.4%) and 73 to 192 months (51.4%) (P<0.05). The cows served in parity 2 to 4 had higher pregnancy rate (57.3%) than those of parity zero (45.0%), 1 (50.0%) and 5 to 10 (46.0%) (P<0.05). Cows yielding 1-3 litres and 4-10 litres of daily milk showed higher pregnancy rate of 67.1 and 65.8%, respectively, followed by those yielding 11 to 34 litres (47.4%) (P<0.05). Pregnancy rate was higher (56.5%) in cows of BCS 3.5 to 4 than those with BCS 2.5 to 3 (48.8%) and BCS 4.5 (50.0%) (P<0.05). Cows served 181 to 270 days after calving had higher (62.7%) pregnancy rate than those served ≤90 days (48.4%), 91 to 180 days (53.7%) and 271 to 780 days (45.5%) (P<0.05). Cows receiving 2nd service had higher pregnancy rate (59.4%) than at 1st (53.3%), 3rd (53.8%) and 4th to 17th (46.4%) services (P<0.05). The cows served in the rainy season had higher pregnancy rate (65.0%) than those served in summer (40.0%) and winter (61.2%) (P<0.05). In conclusion, the present pregnancy rate in cows can be regarded as satisfactory. However, the factors affecting pregnancy rate negatively in commercial farms should be kept in mind for profitable dairying in Bangladesh. The Bangladesh Veterinarian (2018) 35(1&2): 25-31